The Journaling Therapy untuk Meningkatkan Self-Compassion pada Remaja Panti di Asuhan - Taufik Khoiruddin Weanind; Fairul Fikam; Ifa Ditta Arimindani; Hanum Bintania Asyifa; Ashari Mahfud; Muslikah (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This research aims to examine journaling therapy as a means to enhance self-compassion among adolescents in orphanages. The study utilizes a qualitative method, employing secondary data obtained from books, journals, and scholarly articles. Based on a literature review, journaling therapy has been shown to improve self-compassion in adolescents. By engaging in activities that involve documenting experiences, feelings, and personal reflections, adolescents can develop a better understanding of themselves and reduce negative emotions. Therefore, the implementation of journaling therapy in orphanages can assist adolescents in enhancing their self-compassion.